PERSPEKTIF MASA DEPAN UNTUK KETERLIBATAN SISWA SMA - Andamari, Stephanie; Savitri, Jane; Cahyono, Maria Yuni Megarini; Tjandraningtyas, Jacqueline Marie (Universitas Islam Indonesia, 2024)
School engagement is an important factor in learning influenced by social and personal contexts, including motivation. Theoretically, future time perspective (FTP) can enhance student motivation. The aim of this research is to determine whether FTP psychoeducation can increase school engagement in high school students. This research uses a quasi-experimental method with a non-equivalent control group design to examine whether FTP in the form of psychoeducation can enhance school engagement. There were 64 students who participated in this research, namely 33 students in the control group and 31 students in the experimental group. The results of the comparative test show that FTP psychoeducation has no effect on school engagement. The characteristics, conditions of students, and the design of FTP psychoeducation modules need to be considered in further research. Suggestions for more research on variables involving internal factors of students to increase school engagement.